Mobility-aware zoned MANET routing protocol - LI Rui; LI Ren-fa (Tongxin xuebao)
Based on requests of MANET and its applications,a mobility-aware zoned MANET routing protocol —MAFZP was proposed,which zoned by the distance to minID node and only a simple basic network topology was maintained.By using nodes’ neighbors information smart and subtly,the protocol’s request delay and control overhead were all descended to O（2R）.Moreover,nodes’ mobility patterns were also used to descend control overhead.At a result,the protocol’s routing request delay and control overhead were very low.